The Effect of Unemployment Insurance on Unemployment: The Case of Federal Supplemental Benefits - Moffitt, Robert; Nicholson, Walter (The Review of Economics and Statistics, 1982)
Robert Moffitt, Walter Nicholson, The Effect of Unemployment Insurance on Unemployment: The Case of Federal Supplemental Benefits, The Review of Economics and Statistics, Vol. 64, No. 1 (Feb., 1982), pp. 1-11